The undertaker's widow - Margolin, Phillip (New York : Doubleday, 1998)
A Portland judge takes a Caribbean holiday without his wife, which turns out to be a mistake. He meets another woman, has an affair, and when she is murdered keeps quiet for fear he will be the suspect. Just what a blackmailer wanted.
Keywords: Women legislators -- Fiction; Trials (Murder) -- Fiction; Oregon -- Fiction; Legal stories; Mystery fiction